Anti-nociceptive and desensitizing effects of olvanil on capsaicin-induced thermal hyperalgesia in the rat - Alsalem, Mohammad; Millns, Paul; Altarifi, Ahmad; El-Salem, Khalid; Chapman, Victoria; Kendall, David A. (BioMed Central, 2016)
Background: Olvanil (NE 19550) is a non-pungent synthetic analogue of capsaicin, the natural pungent ingredient of capsicum which activates the transient receptor potential vanilloid type-1 (TRPV1) channel and was developed as a potential analgesic compound. Olvanil has potent anti-hyperalgesic effects in several experimental models of chronic pain. Here we report the inhibitory effects of olvanil on nociceptive processing using cultured dorsal root ganglion (DRG) neurons and compare the effects of capsaicin and olvanil on thermal nociceptive processing in vivo; potential contributions of the cannabinoid CB1 receptor to olvanil’s anti-hyperalgesic effects were also investigated. Methods: A hot plate analgesia meter was used to evaluate the anti-nociceptive effects of olvanil on capsaicin-induced thermal hyperalgesia and the role played by CB1 receptors in mediating these effects. Single cell calcium imaging studies of DRG neurons were employed to determine the desensitizing effects of olvanil on capsaicin-evoked calcium responses. Statistical analysis used Student’s t test or one way ANOVA followed by Dunnett’s post-hoctest as appropriate. Results: Both olvanil (100 nM) and capsaicin (100 nM) produced significant increases in intracellular calcium concentrations [Ca2+]I in cultured DRG neurons. Olvanil was able to des ensitise TRPV1 responses to further capsaicin exposure more effectively than capsaicin. Intra plantar injection of capsaicin (0.1, 0.3 and 1μg) produced a robust TRPV1-dependant thermal hyperalgesia in rats, whilst olvanil (0.1, 0.3 and 1μg) produced no hyperalgesia, emphasizing its lack of pungency. The highest dose of olvanil significantly reduced the hyperalgesic effects of capsaicin in vivo. Intraplantar injection of the selective cannabinoid CB1 receptor antagonist rimonabant (1μg) altered neither capsaicin-induced thermal hyperalgesia nor the desensitizing properties of olvanil, indicating a lack of involvement of CB1receptors. Conclusions: Olvanil is effective in reducing capsaicin-induced thermal hyperalgesia, probably via directly desensitizingTRPV1 channels in a CB 1 receptor-independent fashion. The results presented clearly support the potential for olvanil in the development of new topical analgesic preparations for treating chronic pain conditions while avoiding the unwanted side effects of capsaicin treatments.